2022
DOI: 10.3390/foods11020169
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Food Waste into 2,3-Butanediol via Thermophilic Fermentation: Effects of Carbohydrate Content and Nutrient Supplementation

Abstract: Fermentation of food waste into 2,3-butanediol (2,3-BDO), a high-value chemical, is environmentally sustainable and an inexpensive method to recycle waste. Compared to traditional mesophilic fermentation, thermophilic fermentation can inhibit the growth of contaminant bacteria, thereby improving the success of food waste fermentation. However, the effects of sugar and nutrient concentrations in thermophilic food waste fermentations are currently unclear. Here, we investigated the effects of sugar and nutrients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…Interestingly, though starch is a polymer of glucose, the Pearson coefficient for starch was r = 0.1581, indicating weak to no correlation. We suspect this is due to the fact that the YNP5-TSU Bacillus strain cannot effectively hydrolyze starch [22]. Our results were similar to a previous study by , where high glucose concentrations in food waste led to a high butanol yield.…”
Section: Food Waste Composition and 23-bdo Correlationsupporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, though starch is a polymer of glucose, the Pearson coefficient for starch was r = 0.1581, indicating weak to no correlation. We suspect this is due to the fact that the YNP5-TSU Bacillus strain cannot effectively hydrolyze starch [22]. Our results were similar to a previous study by , where high glucose concentrations in food waste led to a high butanol yield.…”
Section: Food Waste Composition and 23-bdo Correlationsupporting
confidence: 91%
“…To circumvent sterilization, thermophilic fermentation has been shown to be effective and involves higher fermentation temperatures (above 45 • C). One such thermophilic bacteria, Bacillus licheniformis YNP5-TSU [22], was shown in a previous experiment to produce yields of 0.31-0.48 g 2,3-BDO/g sugar from various food wastes (pepper, pineapple and miscellaneous wastes) [21] while also eliminating the sterilization step. However, wastes were from pre-consumer stages during refrigerated preparation of meals.…”
Section: Billion Metric Tons Andmentioning
confidence: 99%
“…In this study, bornyl acetate was detected in rancid rather than normal samples, which strongly confirmed that δ -limonene was oxidized and degraded during the rancidity process. In addition, 2,3-butanediol, as high-value chemical, has great potential for diverse industries, including food, cosmetics, agriculture, and pharmaceutical areas [ 43 ]. ( R , R )-2,3-Butanediol and ( R , S )-2,3-butanediol were often detected in foods or TCMs as typical volatile compounds [ 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that, while conducting a non-sterile fermentation using non-sterile food waste using a thermophilic Bacillus licheniformis YNP5-TSU, the 2,3-BDO production was less in comparison with sterile conditions [ 34 ]. An improvised study using the same bacteria showed a significant increase in 2,3-BDO production because of the increase in initial sugar concentration in the hydrolysate [ 35 ]. It showed the effect of hydrolysis and media components on the diol titers.…”
Section: Discussionmentioning
confidence: 99%